Los padres confían en la institución para sus hijos (VITAL, 2025)
The Universidad Antonio Nariño (UAN) is a place where interesting life stories unfold, exemplified by professors whose children also study there. One such story is that of Dr. Francisco Vargas, a Venezuelan veterinary medicine expert. After a distinguished career and facing challenges in Venezuela, he found a new home at UAN eight years ago. His daughter, also began her medical studies there, supported by the university, and recently graduated, with her proud father presenting her diploma.Another compelling narrative is that of Dr. Jorge Guarín, a physician with a master's in pharmacology. After extensive experience in pharmaceuticals and community health, he joined UAN nearly 20 years ago, driven by a passion for teaching. His son, who also studied medicine at UAN, is now a successful emergency specialist, showcasing the university's impact on their shared medical journey. These stories highlight the UAN's role in fostering academic and family legacies.